Barreiras e facilitadores para a adoção de compras sustentáveis: percepção de servidores de instituições federais de ensino - Prass, Márcia Scholten (2025)
There is a growing demand for the public sector to adopt sustainable public procurement, given its importance for sustainable development. In Brazil, sustainable procurement became the norm with the advent of the new General Law on Bidding and Contracts (Law No. 14.133/2021). The literature has sought to identify the barriers and drivers of sustainable practices in public procurement. This dissertation aims to investigate which barriers and facilitators affect sustainable public procurement in federal education institutions (FEIs) and their relationship with employees. To this end, a systematic literature review and bibliometric analysis were carried out, and a research questionnaire was applied to 181 employees of two IFEs in Rio Grande do Sul: the Federal University of Santa Maria (UFSM) and the Farroupilha Federal Institute (IFFar). In the bibliometric analysis, with the aid of the VOSviewer® software, 6 clusters related to barriers and facilitators in sustainable procurement were identified: innovation, practices, implementation, requirements, mediators, and supply chains. This research adopted a cross-sectional quantitative approach, conducted using a structured questionnaire adapted from Roman (2017) and Delmonico et al. (2018). An empirical model was tested through multivariate tests and Structural Equation Modeling (SEM), composed of nine hypotheses. The hypotheses tested the influence of cultural barriers, institutional leadership, and supplier relationships on procurement practices, innovation, and the strategic function of public procurement, and all were accepted. The results show that cultural barriers negatively impact sustainable practices, innovation, and the strategic function of public procurement, indicating that institutions need to promote cultural changes geared towards sustainability. From this perspective, institutional leadership emerges as a determinant for these three factors, highlighting that change in institutions must be sponsored from the top. Another important result concerns collaboration between suppliers and buyers, which highlights the need to improve communication channels and bidding regulations to support procurement with sustainable criteria. The research results offer relevant theoretical contributions, as well as practical recommendations for managers of FEIs, such as investment in training, the institutionalization of sustainable values, and improved communication with suppliers. To minimize the gap identified in the research regarding the low application of the Sustainable Logistics Plan, a repository of sustainability criteria to be applied in public procurement is proposed as a technological product, developed from a diagnosis of public procurement. Limitations of the research include the small sample size and the restriction to only two FEIs. Future research could broaden the scope to other institutions, enabling comparative analyses.